Beginning iOS 5 application development - Lee, Wei-Meng (Wrox beginning guides, 2012)
The ideal starting point for iPhone and iPad app development with iOS 5If you want to develop apps for Apple's iPhone and iPad, first you need to know how to use the tools--iPhone's new iOS 5 operating system and SDK, and the new xCode toolset that come with it. This full-color book is the perfect starting point. Beginning developers, you'll get a solid introduction to the new xCode 4 and Objective-C and find everything you need to quickly build your first app. The book thoroughly covers all the new iOS 5 features, including new multitasking, location-based services, notification system, cloud